Paradigm Shift. The New Promise of Information Technology - Hurtubise, Rolland (Relations industrielles / Industrial Relations, 1993)
The article reviews the book, "Paradigm Shift. The New Promise of Information Technology," by Don Tapscott and Art Caston.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z; information technology